Utilization and trends in surgical instrument use in pediatric adenotonsillectomy. (September 2017) - Walner, David L.; Mularczyk, Christopher; Sweis, Auddie
Abstract: Objective: Examine trends in surgical instrument usage for pediatric adenotonsillectomy. Methods: An online survey asking questions about current and previous surgical instrument use was created by the authors and distributed to 517 members of the American Society of Pediatric Otolaryngology in October 2015. The survey was designed to assess trends in the use of surgical instruments in pediatric adenotonsillectomy by comparing the results of our 2015 survey to data from a previously published 2005 study. Results: 133 surveys were returned. The most common instruments for total tonsillectomy in 2015 were monopolar electrocautery (57.0%) and coblation (22.7%). The most common subtotal tonsillectomy instruments in 2015 were microdebrider with monopolar electrocautery (41.3%) and coblation (37.0%). The most common adenoidectomy instruments in 2015 were monopolar electrocautery alone (41.3%), coblation (15.1%), and microdebrider with electrocautery (15.1%). Conclusion: As compared to our 2005 study, our 2015 study demonstrates that the instrument choice for total tonsillectomy, sub-total tonsillectomy, and adenoidectomy have shifted away from cold techniques toward monopolar electrocautery and coblation.